Clinicopathological and molecular analysis of microsatellite instability in prostate cancer: a multi-institutional study in China - Zhang, Huizhi; Yang, Xiaoqun; Xie, Jialing; Cheng, Xiao; Chen, Jiayi; Shen, Miaomiao; Ding, Wenyi; Wang, Suying; Zhang, Zhe; Wang, Chaofu; Zhao, Ming (Frontiers in Oncology, 2023)
Background: Microsatellite instability (MSI), or mismatch repair-deficiency (dMMR), is rare in prostate cancers (PCas). The histological and molecular features of PCas with MSI/dMMR are incompletely described. Thus, we sought to identify the characteristics of PCas with MSI/dMMR. Methods and Results: We analyzed 1,141 primary treatment-naive PCas by MMR-related protein immunohistochemistry (MLH1, PMS2, MSH2, and MSH6). We identified eight cases exhibiting MSI/dMMR (0.7%, 8/1141). Of these, six tumors had both MSH2 and MSH6 protein loss, one had both MLH1 and PMS2 protein loss, and one had only MSH6 loss. Histologically, MSI/dMMR-PCas frequently demonstrated high histological grade (Grade Group 4 or 5 ), ductal/intraductal histology (6/8 cases), pleomorphic giant-cell features (4/8 cases), and conspicuous tumor lymphocytic infiltration (8/8 cases). Polymerase chain reaction-based analysis of seven MSI/dMMR tumors revealed two MSI-H tumors with loss of both MSH2 and MSH6 proteins. Subsequently, the seven cases underwent next-generation sequencing (NGS) analysis with a highly validated targeted panel; four were MSI. All cases had a high tumor mutation burden (median: 45.3 mutations/Mb). Overall, the MSI/dMMR-PCas showed a high frequency of DNA damage-repair pathway gene changes, including five with pathogenic somatic or germline MMR gene mutations. Activating mutations in the MAPK pathway, PI3K pathway, and WNT/β-catenin pathway were common. TMPRSS2::ERG rearrangement was identified in one case (1/7, 14.3%). Conclusions: Several pathological features are associated with MSI/dMMR in PCas. Identification of these features may help to select patients for genetic screening. As MSI/dMMR-PCas are enriched for actionable mutations, patients should be offered NGS to guide standard-of-care treatment.